HUKUM KESEHATAN DAN AKSES KE OBAT: TINJAUAN EKONOMI TERHADAP HAK PASIEN - Riyan Ardiansyah; Aryono; Juliasti Kinasih Lisa Mutia Sari (Proceedings Law, Accounting, Business, Economics and Language, 2025)
This article discusses the relationship between health law and access to medicines from an economic perspective, with a primary focus on protecting patients' rights in Indonesia. Although the right to health is guaranteed in the constitution and various regulations, its implementation still faces serious challenges due to distribution inequalities, high medicine prices, and weak oversight of the pharmaceutical industry. Market mechanisms that dominate the medicine sector often conflict with principles of justice and humanity, making medicines a commodity that is difficult for low-income communities to access. Government policies such as the e-catalog system and National Health Insurance have been implemented to address this issue, but they have not yet been able to fully guarantee the availability and affordability of medicines in a equitable manner. Therefore, a legal strategy that is more oriented toward economic justice is needed, including strengthening regulations, monitoring distribution, developing national drug production, and actively involving the community in oversight. This study concludes that the law must serve as a state instrument that is not only normative but also solution-oriented, fair, and aligned with the health needs of all citizens.